Detection of Scabies: A Systematic Review of Diagnostic Methods - Victor Leung; Mark Miller (Canadian Journal of Infectious Diseases and Medical Microbiology)
This study systematically reviewed the accuracy and precision of history, physical examination and tests for diagnosing scabies. Using a structured search strategy, Medline and Embase databases were searched for English and French language articles that included a diagnosis of scabies. Studies comparing history, physical examination and/or any diagnostic tests with the reference standard of microscopic visualization of mites, eggs or fecal elements obtained from skin scrapings or biopsies were included for analysis. History and examination of pruritic dermatoses failed to accurately diagnose scabies infection. The accuracy of dermatoscopy, performed by a trained practitioner, was determined; however, the accuracy of other diagnostic tests could not be calculated from the data in the literature. In the face of such diagnostic inaccuracy, research to identify or develop accurate diagnostic tests for scabies infection is needed and justifiable.